Variations Between Adult Day Services Centers in the United States by the Racial and Ethnic Case-Mix of Center Participants. (September 2021) - Lendon, Jessica Penn; Rome, Vincent; Sengupta, Manisha
This is the first nationally representative study to identify differences between adult day services centers, a unique home- and community-based service, by racial/ethnic case-mix: Centers were classified as having a majority of participants who were Hispanic, non-Hispanic Black, or non-Hispanic other race/ethnicities and non-Hispanic White. The associations between racial/ethnic case-mix and geographic and operational characteristics of centers and health and functioning needs of participants were assessed using multivariate regression analyses, using the 2014 National Study of Long-term Care Providers' survey of 2, 432 centers. Half of all adult day centers predominantly served racial/ethnic minorities, which were more likely to be for-profit, had lower percentages of self-pay revenue, more commonly provided transportation services, and had higher percentages of participants with diabetes, compared with predominantly non-Hispanic White centers. Findings show differences by racial/ethnic case-mix, which are important when considering the long-term care needs of a diverse population of older adults.